2002
DOI: 10.1159/000067602
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Suspicion of Gallbladder Carcinoma in Laparoscopic Surgery: What to Do?

Abstract: The frequency of gallbladder cancer in Europe is less than 1% of all gallstone operations. With the introduction of laparoscopic surgery and the higher acceptance of this technique, patients with gallstones have gallbladder removal much earlier in their gallstone history. So the percentage of gallbladder carcinomas will decrease in the future. We report on our surgical procedures in patients with suspicious gallbladders having laparoscopic gallbladder removal, and how to proceed after the diagnosis of gallblad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 9 publications
0
27
0
1
Order By: Relevance
“…F, female; GBP, gallbladder polyp (polypoid lesion); GS, gallstone; Hx, resection of the gallbladder bed with lymph node dissection following LC; LC, laparoscopic cholecystectomy; M, male; pap, papillary adenocarcinoma; pN0, no regional lymph node metastasis; pN2, metastases in peripancreatic (head only), periduodenal, periportal, coeliac and/or superior mesenteric lymph nodes; pNx, regional lymph nodes cannot be assessed; por, poorly differentiated adenocarcinoma; pT2, the tumor invades perimuscular connective tissue without extension beyond the serosa or into the liver; pT3, the tumor perforates the serosa or directly invades one adjacent organ (or both); well, well-differentiated adenocarcinoma. and for patients undergoing LC, unsuspected GBC has been detected in 0.2-2.9% of patients [2][3][4][5]8,18,19]. Among patients presenting with polypoid lesions of the gallbladder, the incidence of cancer is reported to range from 4 to 18% [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…F, female; GBP, gallbladder polyp (polypoid lesion); GS, gallstone; Hx, resection of the gallbladder bed with lymph node dissection following LC; LC, laparoscopic cholecystectomy; M, male; pap, papillary adenocarcinoma; pN0, no regional lymph node metastasis; pN2, metastases in peripancreatic (head only), periduodenal, periportal, coeliac and/or superior mesenteric lymph nodes; pNx, regional lymph nodes cannot be assessed; por, poorly differentiated adenocarcinoma; pT2, the tumor invades perimuscular connective tissue without extension beyond the serosa or into the liver; pT3, the tumor perforates the serosa or directly invades one adjacent organ (or both); well, well-differentiated adenocarcinoma. and for patients undergoing LC, unsuspected GBC has been detected in 0.2-2.9% of patients [2][3][4][5]8,18,19]. Among patients presenting with polypoid lesions of the gallbladder, the incidence of cancer is reported to range from 4 to 18% [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that preoperative diagnosis of gallbladder carcinoma is difficult. Kraas et al (30) reported that gallbladder malignancy is most commonly suspected intraoperatively or diagnosed postoperatively after pathological examination of the resected gallbladder. Ultrasonography is usually unsuccessful in the early detection of gallbladder cancer, especially if inflammation is present (31,32).…”
Section: Mostmentioning
confidence: 99%
“…It is well known that in the almost cases, the surgeon can perfectly suspect this cancer after opening the gallbladder. It is macroscopically apparent on the mucosa of the gallbladder in almost cases [2,3,6,7,11,12]. In our series, it was the case (macroscopically visible) in 29 cases (87.8%) after the opening of the gallbladder by the surgeon.…”
Section: Discussionmentioning
confidence: 45%
“…The prognosis of this form of gallbladder cancer is excellent with a cholecystectomy [2,11,14,16,18] and radical cholecystectomy. The 5 year survival fluctuates between 70% and 100% [2,7,8,11,14,[16][17][18][19][20][21]26]. In our experience, we encountered one death (radical cholecystectomy) not related to the surgery (myocardial infarction).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation